Developing Technology for Special Beer Brewing by Using Non-Traditional Raw Materials - Ter-Movsesyan, H. Zh. (ՀԱԱՀ հիմնադրամ)
The current work aims to justify special beer production technology developed through brier hips and juice. Availability of abundant species of brier hips and juice production industry in the Republic of Armenia enables to use them as non-traditional raw materials for beer brewing. The studies have shown that the most rational way of using brier juice is to add it at beer maturation stage after main fermentation. The most complete, consistent and inherent beer taste has been formed when combining 70 % young beer and 30 % brier juice. Brier hips were added 5 minutes before the end of boiling wort with hops. The best indicators have been recorded in the samples where 0.5 kg brier hips per 1 dal hopped wort has been added.
Keywords: Food Science and Technology